Study on Load-Bearing Characteristics and Engineering Applications for Cement–Soil Pipe Pile - Chong Zhou; Xiangzhuo Zheng; Sifeng Zhang; Chao Li; Yaohui Yang; Jianyong Han (Buildings)
The cement–soil pipe pile is a novel blend of cement and soil, designed to enhance load-bearing capabilities while cutting down on the need for cement. Its tubular construction is key to its strength. To delve into how the pile’s cross-sectional size affects its load-bearing properties, we took into account the soil–cement’s strain-softening behavior. Laboratory tests examined the load-bearing properties of piles. We created an exponential decay Mohr–Coulomb model in ABAQUS for further development, performed field tests, and built a numerical model incorporating wall thickness, pile diameter, and length. The unit volume ultimate bearing capacity was used to evaluate pile performance, with a focus on a 600 mm diameter pile. The results show that wall thickness minimally affects load-bearing capacity, needing to be at least a quarter of the diameter. Larger diameters increase the ultimate bearing capacity, but the capacity per unit volume declines. The 600 mm diameter pile boasts the highest unit volume ultimate bearing capacity. The pile’s effective length is roughly 10 m. Beyond this, extending the pile length increases the single pile’s ultimate bearing capacity by less than 5%, but the unit volume capacity starts to dwindle.